Pengaruh Komunikasi Simentris, Komunikasi Transparan Pada Isu Vaksin Covid 19 Terhadap Hubungan Pemerintah - Warga Negara - Yudi Syahrial; Elizabeth Goenawan Ananto (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This thesis explains how important the effect of positive and significant Symmetrical Communication, Transparent Communication, Government Citizen Relationship, and Citizens' issue specific trust, Constraint recognition, Problem recognition and Involvement recognition are. This thesis describes the effect of symmetrical communication and transparent communication that can help government organizations how to respond to the problems faced by their citizens and how to provide policy information that is useful for making the right decisions, and it will encourage long-term bonds between government organizations and citizens. country so as to enable government organizations to understand the impact of policies that have been made on society This thesis shows from the whole development of 8 (eight) hypotheses, there are 7 (seven) findings that have a direct effect and one indirect hypothesis has a positive and significant effect. The seven variables were developed into 35 measurement indicators and there were 8 (eight) hypotheses tested to produce useful communication designs for government organizations. This study used 340 respondents who were sampled in this study. The findings of this research show that the entire from the development of 8 (eight) hypotheses related to the direct effect proved to have a completely positive significant effect and/or the hypothesis is proven. From the resulting model, it has been proven that a number of variables that have an indirect effect, namely Transparent Communication, mediate the relationship between Symmetrical Communication and Government Citizen Relationship.